Combining Heat Treatment and High-Pressure Torsion to Enhance the Hardness and Corrosion Resistance of A356 Alloy - Mohamed Abdelgawad Gebril; Mohd Zaidi Omar; Intan Fadhlina Mohamed; Norinsan Kamil Othman; Osama M. Irfan (Metals, 2022)
A356 aluminium alloy is subjected to heat treatment and high-pressure torsion (HPT) processing to investigate the impact of the combined treatments on the alloy’s microstructure refinement, corrosion resistance and hardness. The high-pressure torsion process was performed at room temperature for 0.75 and 5 turns. Subjecting the A356 Al alloy to a heat treatment and subsequent HPT processing produced a more refined microstructure, which has the effect of enhancing the alloy hardness and corrosion resistance under fragmentation and the homogenous redistribution of the intermetallic compounds and the Si particles. The results of the treatment show that there is a marked increase in hardness when imposing a strain from 61 HV to 198 HV on the A356 Al alloy, which has been HPTed and heat-treated for five turns. The polarisation curves show that there is a considerable improvement in the corrosion resistance rate of the alloy from 0.043 mm·year−1 for the A356 Al alloy sample to 0.003 mm·year−1 after five turns of HPT. In this work, the microstructure refinement resulted in the improvement of both the mechanical strength and corrosion resistance of the aluminium 356 alloy after heat treatment in comparison to the untreated alloy.